Forming the Sakinah Household In the Perspectives of KH. M. Hasyim Asy'ari - Muhammad Abror Rosyidin (Nusantara: Indonesian Journal of Islamic Studies, 2022)
Abstract This research to explain the ideas of KH. M. Hasyim Asy'ari regarding marriage in Islam, to explain the thoughts of KH. M. Hasyim Asy'ari regarding the sakinah household, explained the relevance of KH. M. Hasyim Asy'ari concerning marriage and sakinah families with Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law (KHI). The Author uses a type of library research, which is descriptive-analytical in nature. While this research approach is a qualitative approach using deductive analysis. The results of his research, that the concept of household according to KH. M. Hasyim Asy'ari relevant to the Act. No. 1 of 1974 concerning Marriage and the Compilation of Islamic Law. The point of relevance lies in the principles and rules of marriage law, the validity of marriage, the rights and obligations of husband and wife, as well as the pillars and conditions of a valid marriage. The four are indicators of a sakinah household Keywords: KH. M. Hasyim Asy'ari, Sakinah Household, Marriage Law, Compilation of Islamic Law.